EXCOMMUNICATION AND CONSCIENCE CONTROL IN MODERN ITALY - Sabato, Milena (European Scientific Journal, ESJ, 2015)
The theme of this research is the main (and oldest) tool of ecclesiastic justice, the penalty most frequently and strategically inflicted in the “fabrication” of ‘docile bodies’” (Fontana, 1977, p. 871): the excommunication, which “holds the main position amongst censorships, or medicinal ecclesiastical penalties, whose main objective is emendation of the offender, and the secondary, his punishment” (Scomunica, 1936, p. 203). In the light of the most recent historiographical debate and with the help of unpublished, rare sources, related to a specific territory in modern Italy, this contribution analyses censorship, “coded” several times during the modern era and inflicted to punish very different sins-crimes, which were very often of a merely secular nature.